2001
DOI: 10.1143/jjap.40.773
|View full text |Cite
|
Sign up to set email alerts
|

The Loss Kinetics of Substitutional Carbon in Si1-xCx Regrown by Solid Phase Epitaxy

Abstract: Epitaxial layers of Si 1−x C x (x = 0.016) were synthesized using ion implantation and solid phase epitaxy (SPE), and the loss kinetics of substitutional carbon was investigated. As annealing temperature and time increase, more carbon atoms were found to diffuse from substitutional to interstitial sites. The activation energy for the loss of substitutional carbon into interstitial sites was obtained over the temperature range, 700-1040 • C, using both high-resolution X-ray diffraction (HR-XRD) and Fourier tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…From previous studies, it was concluded that the major pathways for strain relaxation are (i) kick-out of C sub from substitutional sites with a transition from intermediate Si-C complexes formation to eventual precipitation of b-SiC over 900 C, 20,21 or (ii) formation of dislocation under thermal treatment over 1000 C. 17 In above cases, loss of C sub is the main fingerprint for strain relaxation, and FTIR has been proven to be a suitable tool for identifying C sub loss by measuring the peak intensity of LVM around 607 cm À1 . 22 As shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…From previous studies, it was concluded that the major pathways for strain relaxation are (i) kick-out of C sub from substitutional sites with a transition from intermediate Si-C complexes formation to eventual precipitation of b-SiC over 900 C, 20,21 or (ii) formation of dislocation under thermal treatment over 1000 C. 17 In above cases, loss of C sub is the main fingerprint for strain relaxation, and FTIR has been proven to be a suitable tool for identifying C sub loss by measuring the peak intensity of LVM around 607 cm À1 . 22 As shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Using a lower temperature iRTP anneal (around 1000 o C) can reduce the loss of carbon from the substitutional site. As annealing temperature and time increases more carbon is found to diffuse from substitutional sites to interstitial sites (8). .…”
Section: Resultsmentioning
confidence: 99%
“…Although fRTP effectively activates implanted phosphorus, it also results in significant loss of substitutional C. iRTP anneal at lower temperature (around 1000 o C) can reduce the loss of substitunal C. As annealing temperature and time are increased, increase of C diffusion from substitutional sites to interstitial sites has been reported. [12,13] ECS Transactions, 75 (8)…”
Section: High Resolution X-ray Diffractionmentioning
confidence: 99%